Colorandes UTC - Andrango Quisaguano, Olger Armando (2016)
The investigation was based on the extraction of coloring natural starting from three vegetables: mortiño (Vaccinium floribundum Kunth), beet (Beta vulgaris var. conditiv) and carrot (Daucus carota) that plows autochthonous cultivations of the county of Cotopaxi, the same ones that possess; antocianinas, betanines and carotenoides that give the characteristic coloration to the food. The method of extraction soxhlet was applied to temperature from 45 to 60°C in the extraction of the natural pigments, using the solvent ethylic alcohol to concentration of 95°, the mosto of (mortiño, beet, carrot) it was taken to the alcoholic solution beginning with the maceration process during protected 24 hours of the light, then it filtered with paper filter Whatman in the bugle of the team, the extracts were obtained starting from 2kg of mortiño, 2kg of beet and 2kg of carrot. Eleven obtained the colorings were carried out the physical-chemical analyses (humidity and total solids) and microbiological (aerobic mesófilos < 10, total colifomes < 10, echerichia coli < 10, molds < 10 and yeasts < 10) in the laboratory of analysis of credited food.